2021
DOI: 10.1155/2021/4090441
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CHOP Reduces Neuronal Apoptosis and Rescues Cognitive Impairment Induced by Intermittent Hypoxia by Inhibiting Bax and Bak Activation

Abstract: Our previous study showed that growth arrest- and DNA damage-inducible gene 153 (GAD153/CHOP) plays an important role in intermittent hypoxia- (IH-) induced apoptosis and impaired synaptic plasticity. This study is aimed at determining which signaling pathway is activated to induce CHOP and the role of this protein in mitochondria-dependent apoptosis induced by IH. In the in vivo study, mice were placed in IH chambers for 8 h daily over a period of 2 weeks; the IH chambers had oxygen (O2) concentrations that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
(41 reference statements)
3
14
0
Order By: Relevance
“…CHOP, as a marker of severe ER stress, also as a transcription factor, controls apoptotic‐related gene expression. It is well known that high levels of CHOP trigger the ER stress‐related cascade in cell apoptosis 38,39 . Our data revealed that Cd treatment increased cleaved caspase 12 level in HepG2.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…CHOP, as a marker of severe ER stress, also as a transcription factor, controls apoptotic‐related gene expression. It is well known that high levels of CHOP trigger the ER stress‐related cascade in cell apoptosis 38,39 . Our data revealed that Cd treatment increased cleaved caspase 12 level in HepG2.…”
Section: Discussionsupporting
confidence: 56%
“…It is well known that high levels of CHOP trigger the ER stress-related cascade in cell apoptosis. 38,39 Our data revealed that Cd treatment increased cleaved caspase 12 level in HepG2. Specifically, GSK2606411, a PERK inhibitor, efficiently inhibited CHOP up-regulation and abrogated Cd-induced ER stressmediated apoptotic cascade, thus restored cell viability (Figure 4).…”
Section: Discussionmentioning
confidence: 60%
“…Among them, CHOP is considered a key molecule in the ERS‐related unfolded protein‐mediated apoptotic pathway (Delbrel et al, 2018; Hu et al, 2019). High CHOP expression promotes apoptosis in various cell types, including cardiac fibroblasts (Olivares‐Silva et al, 2021), vascular smooth muscle cells (Tan et al, 2021), and neuronal cells (Xu et al, 2021). We detected the level of trophoblast apoptosis using Hoechst 33342 staining and flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent ER stress-induced PERK activation and concomitant downstream eIF2α/ATF4/CHOP activation play vital roles in promoting neuronal apoptotic death ( 43 – 45 ). CHOP, a transcription factor downstream of the PERK/ATF4 pathway, is thought to be essential to ER stress-induced apoptosis, as its depletion or inhibition attenuates tissue insults in response to ER stress ( 46 49 ). Downregulation of CHOP using siRNA significantly reduced neuronal apoptosis in a mouse model of intracerebral hemorrhage (ICH) ( 50 ).…”
Section: Role Of Endoplasmic Reticulum Stress In Neuronal Deathmentioning
confidence: 99%